1917 Idaho Sess. Laws 461 - (:unkn) unknown (My University, 1917)
An Act . . . To Regulate the Use and Carrying of Concealed Deadly Weapons: Prohibited the concealed carry of any dirk, dirk-knife, Bowie-knife, dagger, slingshot, pistol, revolver, gun, or any other deadly or dangerous weapon
Keywords: CARRY - CONCEALED